PERBANDINGAN ANTARA MAHKAMAH AGUNG DAN MAHKAMAH KONSTITUSI SEBAGAI BAGIAN DARI PELAKU KEKUASAAN KEHAKIMAN DI INDONESIA - HANDOKO, DUWI (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
The 1945 Constitution of the State of the Republic of Indonesia Year 1945 confirms that Indonesia is a country of law. The one important principle of state of law is the guarantee of the implementation of independent judicial power, free from the influence of other powers to organize judiciary to enforce the law and justice. This study is based on the curiosity of investigators in uncovering the scope and existence of judicial power in Indonesia. The scope and existence were restricted to two state institutions in the field of the judiciary, the Supreme Court (SC) and the Constitutional Court (CC). Therefore, this study aims to identify and analyze the comparison (similarities and differences) between the authority of the SC and the CC. This study views of its kind is a normative legal research. While the views of nature, descriptive study. SC and the CC have the same authority to be a court decision that is both first and last. SC and the CC provides access to people who can not afford as the recipient of legal aid to be able to act. SC have jurisdiction in the enforcement of the criminal law, while the CC, does not have jurisdiction in the enforcement of the criminal law, but the CC decision related to the decriminalization of significant influence in the enforcement of criminal law. SC and the CC differ in their patterns and the supervision of the Chief Justice of the Constitutional Court. SC and the CC different in terms of a court decision is final and binding. The SC decision, are not the first and last because is final and binding and there is also not final but is already binding. There are differences of transparency in the legislation review in the SC and the CC. Keywords: The Rule of Law, Attribution Power, Judicial Power, Justice.